Da Pena à Espada: Xenofonte e a Representação de Esparta em A Constituição dos Lacedemônios - Silva, Cleyton Tavares da Silveira (2012)
We intend to analyze how, through your own views and social practices, Xenophon composed the image of Spartans and their poliad regime during the period following the end of the 5th century to the early 4th century before BCE a time of great political turbulence in the Hellenic Poleis. In order to do so, we will use the writings in The Constitution of the Lacedaemonians, to point three elements that we believe are essential understanding of the Xenophon´s narrative: who was Xenophon and in which ways his life experiences influenced his narrative style; the idea of City, i.e., Xenophon´s idea of the Polis and how he defined it as a community of Citizens; and finally, to establish through which tools Xenophon build an image of Sparta and Spartans by way of their representations in his writings